Gregg college keyboarding & document processing (New York, 2002)
Software user's guide for use with Windows 95/98/NT/2000/ME/XP, Internet ready version for home use.
Keywords: Word processing,Keyboarding,Đánh máy,Xử lý văn bản; Problems, exercises, etc.,Problems, exercises, etc.,Vấn đề, bài tập,Vấn đề, bài tập